METODOLOGIA PRELIMINAR PARA O ESTUDO DA MOBILIDADE DE METAIS PESADOS NA ZONA NÃO SATURADA EM CLIMA TROPICAL - Szikszav, Mária; Alexandre, G. A. L.; Hypolito, R.; Toledo-Groke, M. C.; Aguiar, D. M. O.; Shimizu, D.; Fernandes, E. D. N.; Orlando, R. C. (Águas Subterrâneas, 1992)
INDISPONÍVEL